Transarterial chemoembolization combined with iodine 125 seeds versus transarterial chemoembolization combined with radiofrequency ablation in the treatment of early- and intermediate-stage hepatocellular carcinoma - Chen, Lei (BMC Gastroenterol, 2020)
BACKGROUND: Transarterial chemoembolization (TACE), radiofrequency ablation (RFA), and iodine 125 seeds implantation are optional treatments for hepatocellular carcinoma (HCC). The aim of this study is to compare the efficacy of the combined treatment of TACE with iodine 125 seeds implantation (TACE-iodine 125) with TACE with RFA (TACE-RFA) in patients with early- and intermediate-stage HCC. METHODS: The study included 112 patients who were diagnosed with early- and intermediate-stage HCC from January 1, 2014, to May 31, 2018. Among them, 38 patients were treated with TACE-Iodine 125, and 74 with TACE-RFA. The efficacy of the two treatment groups was retrospectively analyzed. To reduced the selective bias, a propensity score matching (PSM) analysis and inverse probability of treatment weighting (IPTW) method were used to compare the outcomes between the two groups. RESULTS: In the absence of PSM and IPTW, the median overall survival (OS) and progression-free survival (PFS) of the TACE-RFA group were slightly longer than those of the TACE-Iodine 125 group (OS: 41 months vs. 36 months; PFS: 18 months vs. 15 months). However, there were no statistically significant differences in the median OS, PFS, and objective response rate (ORR) between the two groups (P > 0.05). After adjusting the age, gender, Child-Pugh class, Barcelona Clinic Liver Cancer (BCLC) stage, and Alpha-fetoprotein (AFP), TACE-Iodine 125 treatment was not associated with a significant increasing the risks of death (HR: 0.763; 95%CI: 0.403,1.345, P = 0.320) and recurrence (HR: 1.020; 95%CI: 0.645,1.611, P = 0.934). After PSM, 35 matched pairs of patients were obtained, and there were no statistically significant differences in the median OS and PFS between the two groups. After IPTW, similar results presented. CONCLUSIONS: The combination of TACE with iodine 125 seeds implantation may represent an effective treatment for patients with early- and intermediate-stage HCC.